Competition and regulatory reform in public utility industries: issues and prospects - Massey, Patrick; O'Hare, Paula (Statistical and Social Inquiry Society of Ireland, 1996)
Throughout the world the electricity, gas and telecommunications industries have undergone dramatic changes over the past twenty years. These changes have involved a major re-appraisal of the role of government regulation in such industries with greater emphasis being placed on promoting competition. Historically in Ireland the public utility industries were public sector monopolies. This position is now set to change due to a combination of technological developments, pressure from the European Commission which is pressing member states to liberalise such industries, and a growing realisation that greater competition in these industries may be beneficial to the economy at large.
Read before the Society, 18 January 1996
Keywords: Public utility industry; Industrial regulation; 314.15